2022
DOI: 10.3389/fonc.2021.789659
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variant Profile of Hereditary Cancer Syndromes in a Vietnamese Cohort

Abstract: BackgroundHereditary cancer syndromes (HCS) are responsible for 5-10% of cancer cases. Genetic testing to identify pathogenic variants associated with cancer predisposition has not been routinely available in Vietnam. Consequently, the prevalence and genetic landscape of HCS remain unknown.Methods1165 Vietnamese individuals enrolled in genetic testing at our laboratory in 2020. We performed analysis of germline mutations in 17 high- and moderate- penetrance genes associated with HCS by next generation sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…There were different hotspot mutations among other populations. They are as follows: BRCA1 c.5251C > T and c.4997dup in the Vietnamese population [ 19 ]; BRCA1 c.4508C > A, c.4065_4068delTCAA, and BRCA2 c.3109C > T, c.4829_4830delTG in the Pakistani population [ 20 ]; BRCA1 c.390C > A, c.3627dupA, and BRCA2 c.7480C > T, c.1399A > T in the Korean population [ 21 ]; BRCA1 c.5123C > A, c.211A > G, and BRCA2 c.2806_2809delAAAC, c.6024dupG in the Spanish population [ 22 ]; BRCA1 c.5123C > A, and BRCA2 c.6174delT in the Latin American and the Caribbean populations [ 23 ]; and BRCA1 c.211dupA, c.798_799delTT, and BRCA2 c.1310_1313delAAGA in the North African population [ 24 ]. In a recent meta-analysis of BRCA1 and BRCA2 gene variations in Chinese individuals, c.5470_5477delATTGGGCA, c.2612C > T, and c.3548A > G in BRCA1 , and c.3109C > T, c.2806_2809delAAAC, and c.5164_5165delAG in BRCA2 were the most common variants [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were different hotspot mutations among other populations. They are as follows: BRCA1 c.5251C > T and c.4997dup in the Vietnamese population [ 19 ]; BRCA1 c.4508C > A, c.4065_4068delTCAA, and BRCA2 c.3109C > T, c.4829_4830delTG in the Pakistani population [ 20 ]; BRCA1 c.390C > A, c.3627dupA, and BRCA2 c.7480C > T, c.1399A > T in the Korean population [ 21 ]; BRCA1 c.5123C > A, c.211A > G, and BRCA2 c.2806_2809delAAAC, c.6024dupG in the Spanish population [ 22 ]; BRCA1 c.5123C > A, and BRCA2 c.6174delT in the Latin American and the Caribbean populations [ 23 ]; and BRCA1 c.211dupA, c.798_799delTT, and BRCA2 c.1310_1313delAAGA in the North African population [ 24 ]. In a recent meta-analysis of BRCA1 and BRCA2 gene variations in Chinese individuals, c.5470_5477delATTGGGCA, c.2612C > T, and c.3548A > G in BRCA1 , and c.3109C > T, c.2806_2809delAAAC, and c.5164_5165delAG in BRCA2 were the most common variants [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were different hotspot mutations among other populations. They are as follows: BRCA1 c.5251C > T and c.4997dup in the Vietnamese population [19]; BRCA1 c.4508C > A, c.4065_4068delTCAA, Hakka population, respectively. These results showed that the hotspots of pathogenic variants in the BRCA genes demonstrate showed race-specific and region-specific differences.…”
Section: Ethnicity Comparison Of Brca1 and Brca2 Pathogenic Variantsmentioning
confidence: 99%
“…Genomic DNA was already isolated from FFPE and WBC samples as previous described [ ( Dang et al, 2020;Nguyen Hoang et al, 2023;Nguyen et al, 2022;Tran et al, 2021)]. DNA fragmentation and library preparation for paired FFPE and WBC samples were performed using the NEBNext Ultra II FS DNA library prep kit (New England Biolabs, USA) following the manufacturer's instructions.…”
Section: Library Preparation and Sequencing For Ffpe And Wbcmentioning
confidence: 99%
“…Germline variants were called from bam files of WBC samples by the DRAGENTM Germline pipeline. Variants were then classified according to the guidelines of The American College of Medical Genetics and Genomics (ACMG) as previously described [ (Tran et al, 2021;]. Pathogenic and likely pathogenic variants were reported.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…According to the National Comprehensive Cancer Network (NCCN) guidelines, the genetic test now incorporates 17 non-BRCA genes (ATM, BARD1, BRIP1, CDH1, CHEK2, EPCAM, MSH2, MLH1, MSH6, NF1, PMS2, PALB2, PTEN, RAD51C, RAD51D, STK11, and TP53) for a comprehensive analysis of the patients [11][12][13] . Globally, there is a tendency to include these genes in large cohorts to elucidate the pathogenicity of HBOC and address better recommendations for patients and their families 14,15 .…”
Section: Introductionmentioning
confidence: 99%